Emerging cardiovascular actions of the incretin hormone glucagon-like peptide-1: potential therapeutic benefits beyond glycaemic control? - Grieve, David J (Blackwell Publishing Ltd, 2009)
Glucagon-like peptide-1 (GLP-1) is an incretin hormone secreted by the small intestine in response to nutrient ingestion. It has wide-ranging effects on glucose metabolism, including stimulation of insulin release, inhibition of glucagon secretion, reduction of gastric emptying and augmentation of satiety. Importantly, the insulinotropic actions of GLP-1 are uniquely dependent on ambient glucose concentrations, and it is this particular characteristic which has led to its recent emergence as a treatment for type 2 diabetes. Although the major physiological function of GLP-1 appears to be in relation to glycaemic control, there is growing evidence to suggest that it may also play an important role in the cardiovascular system. GLP-1 receptors (GLP-1Rs) are expressed in the heart and vasculature of both rodents and humans, and recent studies have demonstrated that GLP-1R agonists have wide-ranging cardiovascular actions, such as modulation of heart rate, blood pressure, vascular tone and myocardial contractility. Importantly, it appears that these agents may also have beneficial effects in the setting of cardiovascular disease (CVD). For example, GLP-1 has been found to exert cardioprotective actions in experimental models of dilated cardiomyopathy, hypertensive heart failure and myocardial infarction (MI). Preliminary clinical studies also indicate that GLP-1 infusion may improve cardiac contractile function in chronic heart failure patients with and without diabetes, and in MI patients after successful angioplasty. This review will discuss the current understanding of GLP-1 biology, examine its emerging cardiovascular actions in both health and disease and explore the potential use of GLP-1 as a novel treatment for CVD.